Pertumbuhan Sengon Umur Lima Tahun pada Tanah Regosol di Widodomartani, Sleman, Yogyakarta - Prijono, Agus; Saputra, Setiaji Heri (Jurnal Wana Tropika, 2024)
Sengon is one of main raw material on wood industry and can be harvested at 5 years.  Another planted at widodomartani ngemplak sleman yogyakarta indonesia with Regosol soil. The aims research were to determine the growth at five years. Planting is done with a distance of 2 x 2 m in the planting hole measuring long and wide with same each 30 cm, 40 cm and 50 cm. The planting hole each used 2 kg and 3 kg compost. The growth data (height and diameter) was taken in each treatment (6 treatments) and each treatment by three repeated. The  data obtained  were analyzed by Anova and if there were significant  differences in factors, followed by LSD test. The analysis showed that the treatment is significant affect to the heigh. The growth rate of Sengon at five years planted is plant height 19.19 m and 18.25 cm diameter. The planting holes 50 cm x 50 cm x 50 cm and 2 kg compost giving optimal result. The best growth of  Sengon treatment is planting 50 cm x 50 cm x 50 cm and 2 kg compost with plant height 24 m and 31.02 cm diameter at the five years plants.